Renewable energy and household economy in rural China. (August 2020) - Huang, Jiashun; Li, Weiping; Guo, Lijia; Hu, Xi; Hall, Jim W.
Abstract: To understand the linkage between renewable energy and economic growth, this study investigates the development of renewable energy, including hydropower, bioenergy, and solar energy, and their effects on rural household economy, by employing a panel data analysis in China during the period of 2003–2017. Based on the evidence of renewable energy infrastructure in the last 20 years, we use a two-way fixed effect model to reveal the relationship between renewable energy investment and household income and consumption. Further, we conduct a panel Granger causality test to verify the impact of renewable energy and economic growth. Empirical results show that investment in renewable energy, including bioenergy, solar energy and hydropower, indeed improve the rural household economy in China. Highlights: The effect of renewable energy on rural economic growth in China is explored. Based on the evidence in the last 14 years, we find effect of renewable energy on rural economy. Rural economics performs better in areas with high renewable energy usage. Reasons that deployment of renewable energy contributes to the rural household economy is explored.